ANGIOGENIC PERACUTE SEPSIS IN AN HIV INFECTED PATIEN - L. V. Puzyreva; V. D. Konchenko; L. M. Dalabaeva (Вестник анестезиологии и реаниматологии, 2018)
The course of sepsis can be peracute in HIV patients, and its initial manifestations could be non-specific (a headache, inadequate behavior etc.) thus it can be difficult to be diagnosed. Sepsis is to be differentiated in intravenous drug users from narcotic intoxication and abstinence. The article presents a clinical case of angiogenic peracute sepsis in a female HIV infected patient, substance abuser, demonstrating that in such patients regardless of their social status the history is to be very carefully taken and thorough clinical examination is to be performed as well as follow-up due to various non-typical manifestations of sepsis.